What Are the Obstacles to Training in Surgery for Congenital Heart Disease in Germany? - Lange, Ruediger; Hoerer, Juergen; Schreiber, Christian (The Thoracic and Cardiovascular Surgeon, 2013)
In recent years, several publications from German institutions have highlighted the need for quality assessment, complexity and risk interpretation, and assurance of sustainable structures in congenital heart surgery. In addition, there is a severe shortage of congenital cardiac surgeons in Germany. To provide quality assurance, the German Society for Thoracic and Cardiovascular Surgery (DGTHG, Deutsche Gesellschaft für Thorax-, Herz- und Gefäßchirurgie) offers a Certificate for Congenital Cardiac Surgery, which is awarded with proof of a minimal number of congenital procedures. We outline that there are too many low-volume centers in Germany putting the cardiac surgeon into the role of a “soloist.” In this situation, adequate training cannot be provided in the majority of the centers in Germany. Furthermore, a considerable reduction of the specifically required operations in the “Weiterbildungsordnung für die Ärzte” (WBO) will be paramount for the future. There should be a stronger consideration for the specific requirements for congenital heart surgeons, to make their training shorter and less cumbersome. Also, the DGTHG's Certificate for Congenital Cardiac Surgery should be tailored to realistic needs in the field of congenital surgery. An adjustment of both the WBO and the Certificate would be in line with the justified claim made in the recommendations of the DGTHG.
Keywords: congenital heart disease; database; mortality; morbidity; training